The relationship between salivary secretion and taste sensitivity level in the elderly - Fimma Naritasari; Dewi Agustina; Supriatno Supriatno (Majalah Kedokteran Gigi Indonesia, 2018)
The increasing population of the elderly has an impact on health problems, including an increase of oral problems. One of the common oral problems is dry mouth that possibly disrupts gustatory function. The aim of this study was to investigate the relationship between salivary secretion and taste sensitivity level in the elderly. This study was a cross sectional study for the elderly population of Daerah Istimewa Yogyakarta/The Special Region of Yogyakarta (DIY) Province, Indonesia. This study consisted of interview, clinical examination, measurement of salivary secretion (sialometry) and taste sensitivity level using chemical gustometry method. Salivary secretion data were described in ml/ min. The measurement of taste sensitivity level was performed using 4 different substances: sweet (sucrose), salty (NaCl), sour (citric acid) and bitter (quinidine sulphate) with 4 different concentrations for each flavor. Four score was given if the respondent recognized the lowest concentration of the substance and 0 score was provided when all concentrations were failed to be tasted. Total score for test sensitivity level was scaled from 0 to 16. Salivary secretion data and taste sensitivity level data were analyzed by Spearman correlation test to determine the correlation between both variables. There were 103 subjects (70 women and 33 men) with the age mean of 65.61 years old, participating in this study. The mean of the sweet taste level was 2.81, 3.32 for salty taste, 3.69 for sour taste and 2.98 for bitter taste. Total taste sensitivity level mean was 12.80 out of 16. The measurements of unstimulated whole saliva showed a mean value of 0.170 ml/min with the majority of subjects having normal salivary flow. The Spearman correlation test results showed r= -0.078 with p >0.05 that indicated no correlation. We concluded that there was no relationship between salivary secretion and taste sensitivity level in the elderly.